Mengukur tingkat kebergunaan website dengan menggunakan metode usability - Rajib Ghaniy; Millatul Aisyi (Teknois : Jurnal Ilmiah Teknologi Informasi dan Sains, 2019)
A website can be used as a tool to convey information, therefore the functionality of a website must be measured, the size of a website, good or not, can be measured by the usability method. In a government website in this case is the website of the district government of mamaju, a simple study of the website of the district of mamaju has been carried out, and the results are found that the website users feel the functionality of the website is said to be lacking, to ensure that what is felt by the user is in this case done further research using the usability method to measure the district of mamaju. The mamaju district website can be visited on page www.mamujukab.go.id , the variable usability method used to measure the website is learnability, efficiency, memorability, errors, and satisfaction. Measurements were made to a sample of website users totaling 74 people, the data analysis technique used was the mean method, and questionnaires were distributed using a Likert scale. From the results of this study, it was found that the learnability value was 2.81, the efficiency value was 2.62, the memorability value was 2.53, the error value was 2.11, and the satisfaction was 2.50. then the overall value obtained at 2.51 which means that the website mamuju district into the category of not good.